EFEKTIVITAS PENGGUNAAN KAHOOT! DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS V SDN NYORMANIS 2 - Fani Nur Anggita; Adhiba Anis Safitri; Fariza Putri Nabila; Amelia Khoiruna; Aisyiyah Siti Rodiyah; Nurhandayany; Ika Dian Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research investigates the effectiveness of Kahoot! in fostering fifth-grade students' learning interest at SDN Nyormanis 2. The study addresses the problem of low student interest, a crucial internal factor influencing academic success. Employing a quantitative approach with an experimental design, data was collected using a closed questionnaire. This instrument, based on a Likert scale (strongly agree (4), agree (3), disagree (2), strongly disagree (1)), measured student responses before and after Kahoot! implementation across indicators such as enjoyment, involvement, attraction, and attention. The findings indicate a significant increase in student learning interest: the average student category shifted from